Evaluation of the Efectiveness Online Class on Fudamental Biophysics Class During COVID 19 Quarantine - Rahmah Evita Putri; Rani Oktavia (SEMESTA: Journal of Science Education and Teaching, 2020)
The purpose of this research is to know the efectiveness of online class on fudamental biophysics class during COVID 19 quarantine. The sample of this research are 70 undergraduate students that is Registered in the even semester of the 2019-2020 school year. The method of this research is qualitative descriptive using google form to collect the data. The result shows that online class on fundamental biohysics during COVID 19 quarantine is not effective. Data shows more than 80% students disagree of studying fundamental biophysic using online class. The data shows that more 50% students not motivated during online learning.